Aspirin and omega-3 polyunsaturated fatty acid use and their interaction in cardiovascular diseases and colorectal adenomas. Issue 2 (13th December 2022) - Wang, Ivan E.; Yi, Shana; Block, Robert C.; Mousa, Shaker A.
Abstract: Aspirin (acetylsalicylic acid, ASA) is inexpensive and is established in preventing cardiovascular disease (CVD) and colorectal adenomas. Omega-3 (n3) polyunsaturated fatty acids (PUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have also shown benefit in preventing CVD. The combination could be an effective preventative measure in patients with such diseases. ASA and n3 PUFA reduced the risk of CVD in ASA-resistant or diabetic patients. EPA- and DHA-deficient patients also benefited the most from n3 PUFA supplementation. Synergistic effects between ASA and EPA and DHA are 'V-shaped' such that optimal ASA efficacy is dependent on EPA and DHA concentrations in blood. In colorectal adenomas, ASA (300 mg/d) and EPA reduced adenoma burden in a location- and subtype-specific manner. Low doses of ASA (75–100 mg/d) were used in CVD prevention; however, ultra-low doses (30 mg/d) can also reduce thrombosis. EPA-to-DHA ratio is also important with regard to efficacy. DHA is more effective in reducing blood pressure and modulating systemic inflammation; however, high-dose EPA can lower CVD events in high-risk individuals. Although current literature has yet to examine ASA and DHA in preventing CVD, such combination warrants further investigation. To increase adherence to ASA and n3 PUFA supplementation, combination dosage form may be required to improve outcomes.